Semiclassical collapse with tachyon field and barotropic fluid - Tavakoli, Yaser (2018)
The purpose of this paper is to extend the analysis presented in Goswami et al. [Phys. Rev. Lett. 96, 031302 (2006)] by means of investigating how a specific type of loop (quantum) effect can alter the outcome of gravitational collapse. To be more concrete, a particular class of spherically symmetric spacetime is considered with a tachyon field ϕ and a barotropic fluid constituting the matter content; the tachyon potential V(ϕ) is assumed to be of the form ϕ^(−2). Within inverse triad corrections, we then obtain, for a semiclassical description, several classes of analytical as well as numerical solutions. Moreover, we identify a subset whose behavior corresponds to an outward flux of energy, thus avoiding either a naked singularity or a black hole formation.